(untitled) (Malay Literature, 2019)
This article aims to analysis the leadership policies practiced by Malay leaders in the traditional prose piece, "Kepimpinan melalui Teladan" ["Leadership by Example"] in the collection titled Antologi Jaket kulit dari Istanbul [Leather Jacket from Istanbul Anthology]. This study was conducted using library research and is a qualitative study focusing on the analysis of texts through characterization, particularly the actions of characters in certain situations. The analysis applied principles of leadership introduced by Mohamad Mokhtar Abu Hassan. The findings show that the Malay leadership of Melaka focused on the dimensions of administration and social responsibility in its leadership practices in order to ensure the continued stability and success of its rule. The administrative dimension is reflected through a leadership that is wise, just, people-centric, strong and kind or generous. The social responsibility dimension is reflected through the leadership’s emphasis on policies concerned with the safety and welfare of the people. It is found that the administrative and social responsibility dimensions are responsible for the success of the leadership’s policies during the glory days of the Melaka Sultanate, which earned it the respect of the other Malay kingdoms. Keywords: administrative dimensions, social responsibility dimensions, leadership principles, leaders, policies